Estimation Method for Metal Damage Struck by Lightning Considering Probability Distribution of Lightning Current Parameters - LI Tianwei (Editorial Office of Journal of Shanghai Jiao Tong University, 2020)
Taking the commonly used metal material aluminum 3003 as an example, and based on the simulated lightning current metal damage test results in the four typical compositions of actual lightning current, the damage characterization parameters such as damage area and damage depth of aluminum 3003 alloy and lightning current parameters were analyzed. Taking the building as an example, and based on the parameter analysis of the combined probability distribution of lightning strike density, lightning interception area, lightning current amplitude and transferred charge amount, the annual average number of lightning strikes and the distribution characteristics of lightning current parameters of metal materials were calculated. A damage estimation method considering the probability distribution of lightning current parameters when a metal material with aluminum 3003 alloy and building carrier as an example was subjected to lightning strikes was established. The results show that the damage depth of the aluminum 3003 alloy material under the action of short-term first return current component and short-duration subsequent return current component is less than 0.1 mm, which can be ignored. The damage area of the aluminum 3003 alloy material is proportional to the magnitude of the lightning current suffered, and the damage depth of the alloy is proportional to the amount of charge transferred by the lightning current.